Intrinsic self-healing thermoset through covalent and hydrogen bonding interactions. (August 2016) - Araya-Hermosilla, R.; Lima, G.M.R.; Raffa, P.; Fortunato, G.; Pucci, A.; Flores, Mario E.; Moreno-Villoslada, I.; Broekhuis, A.A.; Picchioni, F.
Graphical abstract: Highlights: Intrinsic self-healing thermosets were prepared via H-bonding and Diels-Alder reversible cross-linking. Furane and/or OH groups functionalized polyketones (PK) were crosslinked with bismaleimide. PK thermosets displayed tunable softening points from 90 to 137 °C. PK thermosets experienced reversible cross-linking using heat as external stimulus. Mechanical properties of PK thermosets remained almost unchanged after DMTA cycles and recycling. Abstract: The intrinsic self-healing ability of polyketone (PK) chemically modified into furan and/or OH groups containing derivatives is presented. Polymers bearing different ratios of both functional groups were cross-linked via furan/bis-maleimide (Diels-Alder adducts) and hydrogen bonding interactions (aliphatic and aromatic OH groups). The resulting thermosets display tuneable softening points (peak of tan (δ)) from 90 to 137 °C as established by DMTA. It is found that the cross-linked system containing only furan groups shows the highest softening temperature. On the other hand, systems displaying the combination of Diels-Alder adducts and hydrogen bonding (up to 60 mol % of OH groups) do not show any change in modulus between heating cycles ( i . e . factually a quantitative recovery of the mechanical behaviour). It is believed that the novelty of these tuneable thermosets can offer significant advantages over conventional reversible covalent systems. The synergistic reinforcement of both interactions resists multiple heating/healing cycles without any loss of mechanical properties even for thermally healed broken samples.